Analisis Implementasi Corporate Social Responsibility Pada Usaha Kecil Menengah Berbasis Pada ISO 26000 - Ayudyah Eka Apsari; Agus Mansur (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2016)
Corporate social responsibility (CSR) is a claim of stakeholders of a company in order for the company to operate not only in the interest of the company shareholders, but also in the interests of the stakeholders such as employees, local communities, government, customers and environment. The CSR can build some positive effect for the company and gives benefits to society. Additionally, the CSR program is one of the company’s ways in realizing its vision and mission. This research explores main factors influencing the implementation of a CSR program based on ISO 26000 ran by a manufacturing company located in Kecamatan Dlingo, Kabupaten Bantul. Regarding societal aspect, the environment is found as the main factor with MSA score of 0.649. Social relationship among employees, on the other hand, is found as the main factor of employees aspect with MSA score of 0.867.